Development of citizenship virtual class (civics) media integrated with problem based learning to improve digital literacy of Pancasila education - Berlian, Muhamad Fiqri; Sukriono, Didik; Untari, Sri (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2026)
This study investigates whether embedding structured digital citizenship scaffolds within a Problem-Based Learning (PBL) framework is associated with gains in students’ cognitive digital citizenship knowledge in Pancasila Education. Drawing on digital citizenship theory, digital literacy is conceptualized as cognitive knowledge encompassing critical evaluation of online information, understanding of digital ethical norms, and civic digital reasoning. A quasi-experimental design was conducted with 60 eleventh-grade students assigned to experimental and control groups. The experimental group participated in CIVICs-based PBL activities integrating verification tasks, ethical dilemma simulations, and structured deliberative discussions, while the control group received conventional instruction. Cognitive digital citizenship knowledge was measured using pretest–posttest assessments. Results indicate that students exposed to the CIVICs-based PBL design demonstrated higher gains compared to those in conventional learning, with a normalized gain in the medium–high category. These findings suggest that aligning digital citizenship dimensions with structured PBL activities may contribute to strengthening students’ cognitive understanding of responsible digital participation in this context. The results of the study show that the CIVICs media received a “very feasible” rating from media experts with a score of 92.5% and from content experts with a score of 90%. Students’ responses to the use of the media were also highly positive, with an average of 87.1%, particularly in the aspect of digital literacy development, which reached 93.3%. The effectiveness test revealed a significant increase in learning outcomes in the experimental class, with an average post-test score of 85.67, higher than the control class, which scored 67.3. In addition, the CIVICs media was rated highly practical with an average score of 88.8%, covering aspects of accessibility, flexibility, and technical support. Students’ digital literacy scores increased from 62.4 in the pretest to 85.67 in the posttest, with a normalized gain value of 0.619, which falls into the medium–high category. These findings indicate that CIVICs media has a positive impact on improving digital literacy as well as the effectiveness of Problem-Based Learning (PBL) in Pancasila education.